AP Human geography : premium prep. (New York : Penguin Random House, 2020)
Ace the 2021 AP Human Geography Exam with this Premium version of The Princeton Review's comprehensive study guide--including 6 full-length practice tests (more than any major competitor) with complete explanations, thorough content reviews, targeted strategies for every question type, and access to online extras. Techniques That Actually Work." Tried-and-true strategies to help you avoid traps and beat the test.
Part I. Using this book to improve your AP score -- Part II. Practice test 1 -- Part III. About the AP human geography exam -- Part IV. Test-taking strategies for the AP human geography exam -- Part V. Content review for the AP human geography exam -- Part VI. Additional practice tests.
Keywords: HUMAN GEOGRAPHY -- EXAMINATIONS -- STUDY GUIDES